LOGISTICS WAREHOUSE LAYOUT DESIGN - Dewinta, Arinda Dewinta (PT. Antis International Publisher, 2024)
General Background: Effective warehouse management is critical for ensuring rapid and efficient logistics operations, especially in disaster response scenarios. Specific Background: Dinas Sosial Provinsi Jawa Tengah, tasked with disaster management support, faces inefficiencies in its warehouse layout, where logistics goods are poorly organized, leading to delays and increased labor costs during the movement and retrieval of items. Knowledge Gap: Current literature lacks focused studies on optimizing government warehouses specifically for disaster response logistics using class-based storage methods. Aims: This study aims to redesign the warehouse layout of the Central Java Social Service using the class-based storage method to improve the efficiency of goods movement and minimize labor costs. Results: The proposed redesign organizes goods into three classes: Class A (Food), Class B (Evacuation Equipment and Family Supplies), and Class C (Blankets), with respective frequencies of 77.47%, 10.99%, and 4.54%. The new layout, based on these classifications, significantly enhances the efficiency of goods retrieval and movement, reducing labor costs. Novelty: This study applies the class-based storage method, traditionally used in commercial warehouses, to a public-sector disaster logistics context, showcasing its potential to improve operational efficiency in government-run facilities. Implications: The findings suggest that implementing class-based storage methods in government disaster warehouses can serve as a model for other regions to streamline logistics processes, potentially improving disaster response times and resource management.